Analysis of Students’ Cognitive Conceptual Understanding on Temperature and Heat Material Using a Four-Tier Multiple Choice Diagnostic Test - Aini, Hikmah; Sabani, Sabani; Solikin, Solikin; Manik, Krisdayanti; Harahap, Resti Amelya; Putri, Rita Ivanka Pratama; Sibagariang, Selpi Andryani Br. (Universitas Pendidikan Mandalika, 2025)
Persistent misconceptions about temperature and heat often undermine students’ progress in thermodynamics. This study therefore analysed Grade-11 learners’ conceptual understanding of these topics using a Four-Tier Multiple-Choice Diagnostic Test, an instrument that registers answer correctness, explanatory reasoning, and confidence on both selections. A descriptive quantitative design was adopted. Thirty students from class XI-34 of SMAN 3 Medan completed a five-item test that had been validated by experts and piloted for clarity; psychometric checks on the study sample confirmed good reliability (Cronbach’s α = 0.88) and adequate item validity (four of five items met the r-table criterion). Responses were coded into four epistemic categories—Understands Concept (UC), Lacks Knowledge (LK), Misconception (MC), and Error (E)—and analysed. Findings show that overall achievement averaged 30 %, with individual scores ranging from 0 % to 80 %. Across the entire data set, only 27.3 % of responses were classified as UC, while 19.8 % fell into LK, 45.3 % into MC, and 8.0 % into E. Item-level analysis revealed that the highest misconception rate (73.3 %) occurred on the question concerning the effect of temperature on objects, whereas the phase-change item yielded the strongest understanding (46.7 % UC, 20 % MC). These results confirm that misconceptions—especially the conflation of heat with temperature—constitute the principal barrier to coherent learning in this cohort. The study underscores the diagnostic power of four-tier instruments and recommends their wider use across other physics domains, enabling teachers to design confidence-sensitive interventions that directly target high-certainty errors and reinforce fragile correct ideas.